Applying the Squad Health Check Model to agile times at a financial institution (Research, Society and Development, 2020)
In this work were discussed through a qualitative approach, instruments to measure maturity in software development using Scrum applied to 17 teams of a mixed economy financial institution. The practice of maturity measurement is already present even in teams that use traditional method of development, using models such as CMMI - Capability Maturity Model Integration and ISO / IEC 15504 among others, but which are quite linear in their levels. Thus, the analyzed company chose to experiment with the use of a more informal and lighter model to holistically obtain the perception of its teams regarding four dimensions: culture, organizational, technical challenges and insights received from customers and users, to highlight improvement needs and subsequent proposition of action plans. The objective of this paper is to analyze the application of Squad Health Check Model (SHCM) in a large financial institution that uses the Scrum method for agile development of digital products. This article discusses the nature of SHCM, its steps, and its application in a specific context.  The results presented are based on the compilation of perceptions of the 17 agile teams that applied the Spotify Squad Health Check Model, which allowed us to verify that the use of the model proposed by Spotify analysts can be adapted to the reality of Brazilian companies because it presented assertive results. Failures and structural difficulties were evidenced by the model that could be found by analyzing the internal processes of the institution.